2020
DOI: 10.1371/journal.pone.0236965
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of completion of four ANC visits based on recommended time schedule in Northern Ethiopia: A community-based cross-sectional study design

Abstract: Background Despite decades of implementation of maternal health care programs, the uptake of antenatal care services based on the recommended gestational age continues to be below the national and regional targets. Thus, this study aimed to assess the prevalence and factors related to the completion of four antenatal care visits among mothers who gave birth 6 months preceding the study. Method We conducted a community-based cross-sectional study using both quantitative and qualitative approaches. The quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
8
21
2
1
Order By: Relevance
“…We found that lower odds of noncompliance of ANC 8+ visits among pregnant women who were under health insurance coverage compared to those among pregnant women who did not get health insurance services. Comparable findings were reported in prior studies [ 56 58 ]. Health insurance is associated with utilization of ANC and health facility delivery services [ 56 ].…”
Section: Discussionsupporting
confidence: 90%
“…We found that lower odds of noncompliance of ANC 8+ visits among pregnant women who were under health insurance coverage compared to those among pregnant women who did not get health insurance services. Comparable findings were reported in prior studies [ 56 58 ]. Health insurance is associated with utilization of ANC and health facility delivery services [ 56 ].…”
Section: Discussionsupporting
confidence: 90%
“…The chance of completing ≥4 ANC visits was higher among pregnant women who had their husbands support/approval for antenatal visits compared to those counterparts. The above result was supported by a prior study done in Yem special wereda/district, Hadiya/South Ethiopia, Northern Ethiopia, 19 , 27 , 28 Jayapura (Indonesia), 29 and Vietnam. 20 The possible reason might be due to women feels confident and increase their health-seeking behavior, these encourage them to attend more antenatal care visits.…”
Section: Discussionsupporting
confidence: 79%
“…This explanation is maintained by previous studies conducted in Ethiopia, where urban women have better access to antenatal care than those women living in rural areas. 7 , 18 Similarly, utilization of at least 4 ANC visits in our study area was much higher than a study in Northern Ethiopia, 19 Vietnam, 20 Nigeria, 21 and Timor-Leste. 22 This discrepancy might be because of the difference in the study setting like time and study area (rural areas).…”
Section: Discussioncontrasting
confidence: 58%
“…However, by the time of the fourth visit, they had experienced the lack of available services and may have tried to reach additional essential services such as ultrasonogram which is primarily available in the private facilities. Other studies conducted in northern Bangladesh and Ethiopia found low coverage of four timely ANC visits despite high uptake of a timely first ANC [ 25 , 42 ]. In Ethiopia, though their first ANC coverage is less than ours, their timely four ANC utilization was notably greater than this study [ 42 ].…”
Section: Discussionmentioning
confidence: 99%